APHORISM AS A MEANS OF VERBALIZATION OF CONCEPT - Khudoyberdiyeva Oydin Ismoil kizi (Web of Journals Publishing, 2024)
The semantic features of aphorisms are described on the example of two language parames, their categorization and classification, as well as defining the specific mental features of each language unit, as well as the different aspects of their semantic field, as well as their theoretical and scientific foundations, are analyzed in this article.
Keywords: Paremiological unit, aphorism, parema, semantic field, classification, wise word.